Looking beyond silybin: the importance of other silymarin flavonolignans - Selc, Michal; Babelova, Andrea (Frontiers in Pharmacology, 2025)
Silymarin, an extract from the seeds of milk thistle (Silybum marianum), has been widely studied and used for its hepatoprotective and pharmacological properties. For decades, both experimental and clinical research has been predominantly focused on a single component, silybin, while other related flavonolignans, such as silychristin, isosilybins, silydianin, dehydrosilybin, and the flavonoid taxifolin, have been understudied. However, these less known components may possess unique or even superior pharmacological activities compared to silybin, including strong antioxidant, anti-inflammatory, antiviral, and selective anticancer effects. Exploring these other constituents beyond silybin may unlock new opportunities for drug discovery and personalized phytotherapy, ultimately advancing the development of next-generation flavonolignan-based therapeutics.